Use of electronic medical record templates improves quality of care for patients with infantile spasms. Issue 1 (January 2021) - Santoro, Jonathan D; Sandoval Karamian, Amanda G; Ruzhnikov, Maura; Brimble, Elise; Chadwick, Whitney; Wusthoff, Courtney J
Background: Infantile spasms (IS) is a neurologic disorder of childhood where time to treatment may affect long-term outcomes. Due to the clinical complexity of IS, care can be delayed. Objective: To determine if the use of electronic medical record templates (EMRTs) improved care quality in patients treated for IS. Method: Records of patients newly diagnosed with IS were retrospectively reviewed both before and after creation of an EMRT for the workup and treatment of IS. Quality of care measures reviewed included delays in treatment plan, medication administration, obtaining neurodiagnostic studies and discharge. The need for repeat neurodiagnostic studies was also assessed. Resident physicians were surveyed regarding template ease of use and functionality. Results: Of 17 patients with IS, 7 received template-based care and 10 did not. Patients in the non-template group had more delays in treatment ( p = 0.010), delay in medication administration ( p = 0.10), delay in diagnostic studies ( p = 0.01) and delay in discharge ( p = 0.39). Neurodiagnostic studies needed to be repeated in 5 out of 10 patients in the non-template group and none of the 7 patients in the template group ( p = 0.04). Surveyed resident physicians reported improved coordination in care, avoidance of delays in discharge and improved ability to predict side effects of treatment with template use. Conclusion: In a single centre, the use of protocolised EMRTs decreased treatment delays and the need for repeated invasive procedures in patients with newly diagnosed IS and was reported as easy to use by resident physicians. Implications: The use of protocolised EMRTs may improve the quality of patient care in IS and other rare diseases.